Bothrops atrox, the most important snake involved in human envenomings in the amazon: How venomics contributes to the knowledge of snake biology and clinical toxinology. (June 2020) - Monteiro, Wuelton Marcelo; Contreras-Bernal, Jorge Carlos; Bisneto, Pedro Ferreira; Sachett, Jacqueline; Mendonça da Silva, Iran; Lacerda, Marcus; Guimarães da Costa, Allyson; Val, Fernando; Brasileiro, Lisele; Sartim, Marco Aurélio; Silva-de-Oliveira, Sâmella; Bernarde, Paulo Sérgio; et al.
Abstract: Bothrops atrox snakes are mostly endemic of the Amazon rainforest and is certainly the South American pit viper responsible for most of the snakebites in the region. The composition of B. atrox venom is significantly known and has been used to trace the relevance of the venom phenotype for snake biology and for the impacts in the clinics of human patients involved in accidents by B. atrox . However, in spite of the wide distribution and the great medical relevance of B. atrox snakes, B. atrox taxonomy is not fully resolved and the impacts of the lack of taxonomic resolution on the studies focused on venom or envenoming are currently unknown. B. atrox venom presents different degrees of compositional variability and is generally coagulotoxic, inducing systemic hematological disturbances and local tissue damage in snakebite patients. Antivenoms are the effective therapy for attenuating the clinical signs. This review brings a comprehensive discussion of the literature concerning B. atrox snakes encompassing from snake taxonomy, diet and venom composition, towards clinical aspects of snakebite patients and efficacy of the antivenoms. This discussion is highly supported by the contributions that venomics and antivenomics added for the advancement of knowledge of B. atrox snakes, their venoms and the treatment of accidents they evoke. Highlights: Bothrops atrox snakes' genetics and ecological aspects are reviewed. Venom composition, isolated toxins and their actions are described. Clinical aspects of B. atrox envenomings are described and illustrated. Contributions of venomics and antivenomics for the knowledge of B. atrox snakes are highlighted.